Trees in the Congo - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Some 96 % of the Congo's export earnings are from offshore oil, but the country is already preparing for the time when oil runs out. Earlier this year, President Nguesso planted the ten millionth tree in a reforestation programme which will allow...